FRAKTAL SEBAGAI SUMBER IDE PENGEMBANGAN DESAIN BATIK TUBAN - Puspa Wardani, Fernanda Rizky (Studi Budaya Nusantara, 2022)
The design for the pattern of Batik Tuban with Fractal visual idea was motivated by the availability of a chance to develop a new design that focuses on the visual processing of Fractals and Batik Tuban motif itself. The urge that generates this idea was taken not only because of the phenomena that Fractals are currently being explored, but also based on the unique characteristics of visual Fractals itself that can produce new various and diverse motifs. Visual Fractals are acquired from a software called